Three-Year-Olds' Understanding of Desire Reports Is Robust to Conflict - Harrigan, Kaitlyn; Hacquard, Valentine; Lidz, Jeffrey (Frontiers in Psychology, 2018)
In this paper, we present two experiments with three-year-olds, exploring their interpretation of sentences about desires. A mature concept of desire entails that desires may conflict with reality and that different people may have conflicting desires. While previous literature is suggestive, it remains unclear whether young children understand that (a) agents can have counterfactual desires about current states of affairs and (b) agents can have desires that conflict with one’s own desires or the desires of others. In this article, we test preschoolers’ interpretation of want sentences, in order to better understand their ability to represent conflicting desires, and to interpret sentences reporting these desires. In the first experiment, we use a truth-value judgment task (TVJT) to assess three-year-olds’ understanding of want sentences when the subject of the sentence has a desire that conflicts with reality. In the second experiment, we use a game task to induce desires in the child that conflict with the desires of a competitor, and assess their understanding of sentences describing these desires. In both experiments, we find that three-year-olds successfully interpret want sentences, suggesting that their ability to represent conflicting desires is adult-like at this age. Given that three-year-olds generally display difficulty attributing beliefs to others that conflict with reality or with the child’s own beliefs, these findings may further cast some doubt on the view that children’s persistent difficulty with belief (think) is caused by these kinds of conflicts.